In Search of a New Cognitive Schema: Unsettling Colonial Epistemologies in Dionne Brand’s A Map to the Door of No Return - Deborah Pomeranz (Current Objectives of Postgraduate American Studies)
In this paper, I argue that Dionne Brand’s A Map to the Door of No Return: Notes to Belonging“ unsettles the epistemic foundations of the (Post-)Colonial Anthropocene, which prioritize linearity, binarity, and purported objectivity. Dominant contemporary epistemologies, as Sylvia Wynter has demonstrated, race and gender legitimate knowledge production as the preserve of Man, to the exclusion of human and non-human others. Instead, writing towards the multipolarity and -modality of the Door of No Return, Brand posits and practices, through both form and content, an anti-colonial epistemology, in which temporality and spatiality are recursive and knowledge is embodied and pluriversal.